Analisis Pengaruh Pelemahan Rupiah terhadap Krisis Ekonomi: Studi Kasus ketika Dollar Tembus Rp18.000 - Ari Bryllianto Falih Hidayat; Nurul Huda; Dewi Puspaningtyas Faeni (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to analyze the impact of the Rupiah’s depreciation on the domestic economic crisis, focusing on import inflation, foreign debt burdens, foreign exchange reserves, and financial sector stability. The study employs a descriptive quantitative method with a case study approach. Data were collected through literature review and analysis of secondary data from Bank Indonesia (BI), the Central Statistics Agency (BPS), the Ministry of Finance, and the IMF for the period 2024–2026. The results indicate that a depreciation of the Rupiah to the level of Rp18,000 per USD leads to an 8–12% increase in import inflation, a rise in corporate debt burdens of 25–30%, a decline in foreign exchange reserves of approximately 15% over three months, and volatility in the stock and bond markets. In conclusion, extreme Rupiah depreciation has a significant impact on the economic crisis, particularly through the mechanisms of import costs, inflationary pressure, and capital outflows. The government and Bank Indonesia are advised to strengthen market interventions, optimize exchange rate stabilization instruments, and accelerate the diversification of foreign exchange sources and import substitution